Використання засобів привернення та утримання уваги аудиторії під час усного виступу - Тінінікіна, А. В. (ХНУРЕ, 2020)
Нow can we create content that will keep audiences engaged? It's the little things; the speaking and body language tricks you use, that will keep your audience awake long enough to hear it.
Keywords: культурне розмаїття; українознавство; традиції; культура